Numerical Investigation of The Effect of Fin Thickness on Straight Fin Heat Sink on Heat Transfer Performance - Muhamad Safi'i; Nazaruddin Sinaga; Tabah Priangkoso; Suheri Suheri; Rouf Muhammad (Universitas Wahid Hasyim, 2025)
The heat load on computer chips during computing performance is the main topic, so a cooling device is needed. Heat sink is one of the tools commonly applied to reduce the heat load during computing performance of computer systems. Various heat sink configurations have been widely developed and studied to obtain designs with the best thermal performance. This research was conducted to investigate the best design on a straight fin heat sink (SFHS) that has the best thermal and hydraulic performance. SFHS with fin thickness variations of 1 mm, 2 mm, and 3 mm are proposed in this study. The numerical method was carried out using the Computational Flui Dynamics program by considering fluid flow velocities of 4 m/s, 6 m/s, 8 m/s and 10 m/s. The numerical results show that the cooling rate of SFHS can be increased by using SFHS with a thickness of 3 mm and a fluid flow velocity of 10 m/s with a maximum Nusselt number value of 59.74. Therefore, it is concluded that the SFHS has prospects for further study and can be applied practically in the field for micro electronic components and computer systems. Keywords: Heat sink, SFHS, Straight fin.